Effect of Er:YAG Laser and Reduced Time of Acid Etching on Bond Strength of Self-adhesive Resin Cement to MTA and Biodentine: Bond Strength of Pretreated MTA and Biodentine - Dehghanian, Paria; Shafiei, Fereshteh; Kianimanesh, Nasrin (Journal of Lasers in Medical Sciences, 2021)
Introduction: Considering the recent trend to use mineral trioxide aggregate (MTA) and Biodentine and resin cements, more conservative approaches concurrent with adequate bond strength have always been requested. The present study aimed to evaluate the effect of pretreatment with Er: YAG laser etching versus acid-etching for 5 and 15 seconds on the micro shear bond strength of selfadhesive resin cement (SRC) to MTA and Biodentine. Materials and Methods: Forty-eight samples of each cement (MTA and Biodentine) were prepared and distributed into four groups based on surface pretreatment: 1) control, no treatment; 2) Er: YAG laser etching with the energy of 60 mJ; 3) 5-second acid-etching; 4) 15-second acid-etching. All specimens were cemented using SRC. Microshear bond strengths were tested following 24-hour water storage. Debonded specimens were examined and surface topography was assessed using an atomic force machine (AFM). Data analysis was performed using the two-way ANOVA and Tukey multiple comparisons test. Results: The three testing groups of laser etch and 5-s and 15-s acid-etch demonstrated a significantly higher SBS than the control group (P<0.05) with negligible differences among them (P > 0.05). Furthermore, Biodentine showed better adhesive bonding than MTA in all groups. Conclusion: Laser etching of 60 mJ and 5-s acid-etching were as beneficial as 15-s acid-etching in terms of bond strength of SRC to MTA and Bodentine. Doi:10.34172/jlms.2021.36